"A Matter of Life and Death": Kawabata on the Value of Art after the Atomic Bombings. Issue 3 (June 2014) - MILLER, MARA
ABSTRACT: This article explores the possible interpretations—and the implications of those interpretations—of a comment about the importance of art made by Yasunari Kawabata (1899–1972), later the first Japanese Nobel laureate for literature: that "looking at old works of art is a matter of life and death." (In 1949, Kawabata visited Hiroshima in his capacity as president of the Japan literary society P.E.N. to inspect the damage caused by the atomic bombing of Hiroshima that helped end World War II. On his way back to his home in Kamakura, he stopped in Kyoto. He came under severe criticism for "sightseeing" at such a time. This comment was his response.) The introduction explains why we should take him seriously as a commentator on art. The body of the article examines why our looking at art might be more, not less, important after the post‐War situation, the kinds of art Kawabata might have meant, why some possibilities are more likely than others, and how they differ in what they offer us and the value of art under conditions of trauma and mass trauma.